Papuan local wisdom and problem-based learning: Integrated into student books and its effect on students' conservation attitudes - Silahooy, Putri Viorela; Nunaki, Jan Hendriek; Jeni, Jeni; Wambrauw, Hengky Lukas; Nasir, Nur Indah Ririn Fitriani; Damopolii, Insar; Siregar, Nahrun Najib; Budirianto, Heru Joko (Inornatus: Biology Education Journal, 2024)
Papua, which is known to be rich in local wisdom, has great potential in environmental conservation if supported by a strong conservative attitude from its citizens. This research aims to determine the influence of problem-based student books integrated with Papuan local wisdom on the conservation attitudes of class VII junior high school students. This research is experimental research conducted at junior high schools in the Tanah Merah area of Bintuni Bay. In this study, the sample used was class VII, consisting of 38 students. There were 19 students in the control and experimental classes each. A conservation attitude questionnaire was used to measure students' conservation attitudes. Data were analyzed using the t test. The results show that problem-based student books integrated with Papuan local wisdom have a better effect than the control class. Local wisdom adds to students' information regarding the management of endemic organisms where they live. The problem of extinction in PBL learning empowers students to think about how to conserve organisms so that extinction factors that influence the classification of living things can be prevented.